Problem-based learning and mathtastic app integration to improve reasoning and collaboration in mathematics learning among primary students: an experimental approach - Wanda Nugroho Yanuarto; Stephanie Prisca Dewi; Subuh Anggoro; Akhmad Jazuli; Masanori Fukui (CV. FOUNDAE, 2025)
Background: This experimental study explores the integration of Problem-Based Learning (PBL) and the Mathtastic application to enhance mathematical reasoning and collaborative skills among primary school students. Aims: Grounded in constructivist learning theory, the research aims to determine the effectiveness of a technology-supported PBL approach in fostering students’ higher-order thinking and teamwork abilities in the context of mathematics education. Methods: The study employed a quasi-experimental design with control and experimental groups comprising Grade 5 students from a public elementary school. The experimental group received mathematics instruction through PBL integrated with the Mathtastic app, while the control group was taught using conventional methods. Data were collected using pre- and post-tests on mathematical reasoning, a collaboration rubric, and observation sheets. Result: The results showed a statistically significant improvement in the reasoning and collaboration performance of students in the experimental group compared to those in the control group. These findings suggest that combining PBL with interactive educational technology like Mathtastic can create a more engaging and effective learning environment for young learners. Conclusion: The study provides practical implications for teachers seeking to integrate digital tools and inquiry-based approaches to enrich mathematics learning experiences at the primary level.